GE_GERICHTE C/7447/2017 vom 27. Mai 2019 - GE Cour de justice (2019)
ADMINISTRATION DES PREUVES;MAXIME INQUISITOIRE;DROIT D'ÊTRE ENTENDU;DÉFAUT DE LA CHOSE | CPC.311.al1; CO.256.al1; CPC.246.al1; CPC.243.al2.letc; Cst.29.al2; CPC.150.al1